Using PC DOS - DeVoney, Chris (Carmel, Ind. : Que Corp., 1987)
Using PC DOS, 2nd edition is an even better version of an already classic text. it is guide that is both comprehensive tutorial and lasting reference.
"Covers version 3.3"--Cover.
include list of tables and appendixes
Includes index.
ijb, 16/01/2019
Loans
Keywords: Computer; Computer studies